Safety of baricitinib for the treatment of atopic dermatitis over a median of 1.6 years and up to 3.9 years of treatment: an updated integrated analysis of eight clinical trials - Thomas Bieber; Norito Katoh; Eric L. Simpson; Marjolein de Bruin-Weller; Diamant Thaçi; Antonio Torrelo; Angelina Sontag; Susanne Grond; Maher Issa; Xiaoyu Lu; Tracy Cardillo; Katrin Holzwarth; et al. (Taylor & Francis Group, 2023)
Background Baricitinib, a selective Janus kinase (JAK)1/JAK2 inhibitor, is approved for treatment of moderate-to-severe atopic dermatitis (AD) in adults. Objectives We report integrated baricitinib safety data in patients with up to 3.9-years exposure. Methods Three datasets from the integrated AD clinical trial program were analyzed: placebo-controlled, 2-mg-4-mg extended, and All-bari. Data cutoffs were up to 21-December-2021 for long-term extension studies. Proportions of patients with events and incidence rates (IR)/100 patient years (PY) at risk were calculated. Results 2636 patients received baricitinib for 4628.4 PY. Discontinuation due to adverse events was low (IR = 3.4). IRs in All-bari were: serious adverse events, 5.2; infection, 67.2 (any infection), 6.7 (herpes simplex), 2.8 (herpes zoster), and 0.3 (opportunistic infections). Adverse events of special interest in All-bari included seven patients with positively adjudicated major adverse cardiovascular events (MACE) (IR = 0.15), three pulmonary emboli (PE) (IR = 0.06), 14 malignancies excluding nonmelanoma skin cancer (IR = 0.3), one gastrointestinal perforation (IR = 0.02), and four deaths (IR = 0.1). No deep vein thromboses (DVT) or tuberculosis were reported. Conclusion In this analysis, baricitinib maintained a similar safety profile to earlier analyses with no new safety signals. Rates of MACE, DVT/PE, malignancies, and serious infections were within ranges of background rates in patients with AD. Clinicaltrials.gov NCT02576938 (JAHG), NCT03334396 (JAHL; BREEZE-AD1), NCT03334422 (JAHM; BREEZE-AD2), NCT03334435 (JAHN; BREEZE-AD3), NCT03428100 (JAIN; BREEZE-AD4), NCT03435081 (JAIW; BREEZE-AD5), NCT03559270 (JAIX; BREEZE-AD6), NCT03733301 (JAIY; BREEZE-AD7)